From Home to Campus: The Impact of Parenting and Self-Efficacy on Student Education Decisions - Ningsih, Sri Mariya; Rejeki, Asri (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Making decisions about further education is a critical phase for students, particularly during the transition from adolescence to adulthood. This process not only defines their educational direction but also impacts their career prospects and future life. This study aims to examine the influence of parenting styles and self-efficacy on further education decision-making among 11th-grade students at SMA Muhammadiyah 8 Gresik. The research employed a quantitative design using multiple linear regression. Data were collected through Likert-scale questionnaires and analyzed using classical assumption tests, multiple regression. The results show that democratic parenting and self-efficacy have a significant positive influence on students’ educational decision-making abilities. In contrast, authoritarian parenting has a significant negative influence, while permissive parenting shows no significant effect. The implications of this study highlight the importance of supportive parenting and the development of students' self-efficacy to help them make informed educational decisions. Schools are also expected to provide psycho-pedagogical support to foster students’ independence and confidence in planning their educational futures.Pengambilan keputusan pendidikan lanjutan merupakan fase krusial yang dihadapi siswa, khususnya pada masa transisi dari remaja menuju dewasa. Proses ini tidak hanya menentukan arah pendidikan, tetapi juga memengaruhi prospek karier dan kehidupan masa depan. Penelitian ini bertujuan untuk mengetahui pengaruh pola asuh dan self-efficacy terhadap pengambilan keputusan pendidikan lanjutan pada siswa kelas XI di SMA Muhammadiyah 8 Gresik. Metode yang digunakan adalah kuantitatif dengan pendekatan regresi linear berganda. Teknik pengumpulan data dilakukan melalui angket dengan skala Likert dan dianalisis menggunakan uji asumsi klasik, regresi berganda. Hasil penelitian menunjukkan bahwa pola asuh demokratis dan self-efficacy memiliki pengaruh positif dan signifikan terhadap kemampuan siswa dalam mengambil keputusan pendidikan. Sementara itu, pola asuh otoriter menunjukkan pengaruh negatif signifikan, dan pola asuh permisif tidak berpengaruh secara signifikan. Implikasi dari penelitian ini adalah pentingnya keterlibatan orang tua dalam memberikan pola asuh yang mendukung serta penguatan self-efficacy siswa untuk membantu mereka membuat keputusan pendidikan yang tepat. Sekolah juga diharapkan mampu menyediakan dukungan psikopedagogis yang mendorong kemandirian dan kepercayaan diri siswa dalam menentukan masa depan pendidikannya.